Renewable energy benefits : leveraging local capacity for solar PV (International Renewable Energy Agency, 2017)
Renewable energy development can drive economic growth, create new jobs and enhance human health and welfare at the national level. The Leveraging Local Capacity series examines the kinds of jobs created and suggests ways to build on existing industries. Each study outlines the requirements along the whole value chain, particularly in terms of human resources and skills, to produce, install and operate plants or facilities based on a certain renewable energy technology. This involves assessing the materials and equipment needed in each segment, with a focus on identifying potential for local value creation.